Political Evolution of Kashmir during the Mughal Period - Kumar, Arun (Integrated Journal for Research in Arts and Humanities, 2023)
The Mughal period in Kashmir's history, spanning from the late 16th to the late 17th century, signifies a transformative phase in the region's political tapestry. With its strategic significance and natural allure, Kashmir invariably drew the attention of Mughal emperors, culminating in its annexation under Emperor Akbar in 1586. This research delves into the consequential shifts in political paradigms during the Mughal reign. It underscores the sophisticated administrative frameworks introduced, exemplified by the 'Mansabdari' system, and the meticulous blend of military strategy with diplomatic outreach to ensure regional stability. Further, the paper highlights the nuanced governance approaches of successive Mughal emperors, delineating their individual contributions and challenges. As the broader Mughal Empire exhibited signs of decline, its reverberations in Kashmir's political scenario are also explored, marking the transition to ensuing power struggles. This study, thus, offers a comprehensive insight into the intricate dynamics that shaped Kashmir's political landscape during the Mughal epoch, emphasizing the empire's lasting legacies and the region's evolution in response to them.